Kedudukan Perawi Majhūl dalam Perspektif Abu Hātim Ar-Rāzi - Wahyudi, Rudi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2020)
In the field of Hadith studies, Abu Hātim ar-Rāzi had its own position that was different from other hadith critics, where he was counted as the first generation of hadith critics. Therefore, he had many terms in the science of hadith that were different from the other who came after him. For example, the term of majhūl which he used a lot in criticizing hadith narrators, as quoted by his son Ibn Hātim ar-Rāzi, did not refer to a certain meaning but had many meanings. Sometimes, Abu Hātim ar-Rāzi used the term of majhul to refer to the narrator whose his hadith only narrated by one narrator afterwards. On the other hand, the term of majhūl sometimes referred to the narrator whose his hadith even narrated by more than six narrators as Ṣālih bin Jubair as-Syāmi. And sometimes it referred literally to a non-famous narrator as Mas’ūd bin ar-Rabī’, a friend of prophet Muhammad PBUH. Even, in the use of the term of majhūl, Abu Hātim ar-Rāzi used many terms. Sometimes he used the sentence “I didn’t know”, “ I didn’t understad him”, “I didn’t know the information about him”, no meaning”, “he was unknowed”, “his house is unknowed”, “he was shaykh”, and others. According to Abu Hātim ar-Rāzi, the narration of the unknown narrator “majhul” was rejected if his term had the same meaning as the others. Di bidang studi Hadits, Abu Hātim ar-Rāzi memiliki posisi yang berbeda dari kritik hadis lainnya, di mana ia dianggap sebagai generasi pertama kritik hadis. Karena itu, ia memiliki banyak istilah dalam ilmu hadits yang berbeda dari ulama lain yang datang setelahnya. Misalnya, istilah majhūl yang banyak digunakannya dalam mengkritik narator hadits, seperti dikutip oleh putranya Ibn Hātim ar-Rāzi, tidak merujuk pada makna tertentu tetapi memiliki banyak makna. Terkadang, Abu Hātim ar-Rāzi menggunakan istilah majhul untuk merujuk pada narator yang haditsnya hanya diriwayatkan oleh satu narator sesudahnya. Di sisi lain, istilah majhūl kadang-kadang menyebut narator yang haditsnya bahkan diriwayatkan oleh lebih dari enam narator sebagai Ṣālih bin Jubair as-Syāmi. Dan kadang-kadang merujuk secara harfiah kepada narator yang tidak terkenal sebagaimana Mas'ūd bin ar-Rabī ', teman nabi Muhammad SAW. Bahkan, dalam penggunaan istilah majhūl, Abu Hātim ar-Rāzi menggunakan banyak istilah. Kadang-kadang dia menggunakan kalimat